Exploring factors predicting the effectiveness of oral semaglutide in Japanese individuals with type 2 diabetes switching from dipeptidyl peptidase 4 inhibitors: a pilot study - Hirotsu, Takao; Taniguchi, Kanta; Nishimura, Rimei (Frontiers in Clinical Diabetes and Healthcare, 2025)
IntroductionOral semaglutide is a glucagon-like peptide-1 receptor agonist (GLP-1 RA) approved for the treatment of type 2 diabetes mellitus (T2DM). Findings from randomized controlled trials (RCTs) and real-world studies indicate that oral semaglutide leads to significant improvements in HbA1c and body weight, comparable to those observed with injectable GLP-1 RAs. Consequently, oral semaglutide is expected to significantly reduce barriers to initiating GLP-1 RA therapy in individuals with diabetes and may lead to an increased transition from dipeptidyl peptidase-4 inhibitors (DPP-4is) to GLP-1 RA therapy. This study was conducted to prospectively investigate the clinical characteristics predicting the achievement of HbA1c < 7% (52 mmol/mol) in Japanese individuals with T2DM who switched from DPP-4is to oral semaglutide.MethodsThe study enrolled a total of 74 patients who switched from DPP-4is to oral semaglutide between December 2021 and October 2022, with the dose being uptitrated to achieve HbA1c < 7% (52 mmol/mol) in these patients.ResultsThe study included a total of 44 individuals who achieved the target with oral semaglutide 3 mg (n=7), 7 mg (n=24), or 14 mg (n=13), and 17 individuals who did not (un-achieved group; n=17), based on their clinical characteristics and hematological findings. In the comparison between the Un-achieved group and the Achieved (3 to 14 mg) group, the proportions of “Current alcohol drinking (p = 0.030)” and “Current alcohol drinking and smoking (p = 0.029)” were higher in the Un-achieved group, whereas the proportion of “Taking 31 minutes or longer to have breakfast after drug administration (p = 0.022)” was higher in the Achieved (3 to 14 mg) group. A logistic regression analysis using the stepwise method identified “No current history of both smoking and alcohol drinking (0.083[0.014-0.485]; p = 0.006)” and “Taking 31 minutes or longer to eat breakfast after drug administration (0.117[0.029-0.480]; p = 0.003)” as factors predicting the achievement of the HbA1c < 7% (52 mmol/mol).ConclusionStudy findings suggest when considering switching T2D patients from DPP-4is to oral semaglutide, a detailed assessment of “current alcohol drinking and smoking status” and “the duration between the administration of oral semaglutide and breakfast” may be useful as a predictive indicator for achieving HbA1c < 7% (52 mmol/mol).